2017
DOI: 10.1002/1878-0261.12071
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells activate the cancer stem cell‐associated NANOGP8 pathway in colorectal cancer cells in a paracrine fashion

Abstract: In colorectal cancer (CRC), cancer stem cells (CSCs) have been hypothesized to mediate cell survival and chemoresistance. Previous studies from our laboratory described a role for liver parenchymal endothelial cells (LPECs) in mediating the CSC phenotype in CRC cells in a paracrine/angiocrine fashion. The objectives of this study were to determine whether endothelial cells (ECs) from different organs can induce the CSC phenotype in CRC cells and to elucidate the signaling pathways involved. We treated a newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…To determine the effects of ECs on CRC cell survival (including cell viability and chemoresistance), we used primary liver EC lines (LPEC-1 and LPEC-6) that our laboratory established from non-malignant liver tissues (10). CM containing EC-secreted factors was harvested and added to CRC cells (HCP-1, HT29 and SW480), with CM from CRC cells themselves serving as control CM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the effects of ECs on CRC cell survival (including cell viability and chemoresistance), we used primary liver EC lines (LPEC-1 and LPEC-6) that our laboratory established from non-malignant liver tissues (10). CM containing EC-secreted factors was harvested and added to CRC cells (HCP-1, HT29 and SW480), with CM from CRC cells themselves serving as control CM.…”
Section: Resultsmentioning
confidence: 99%
“…The colorectal cancer (CRC) cell lines SW480, HT29, HCT116, RKO, SW48 and Caco2 were purchased from American Type Culture Collection (ATCC, Manassas, VA). The H uman C RC P rimary cell line (HCP-1), luciferase-labeled HCP-1 cells, L iver P arenchymal E ndothelial C ell (LPEC-1 and LPEC-6) lines, ECs from lung (lung ECs), and ECs from colon mucosa (colon ECs) were established in our laboratory (10,11). CRC cells were cultured in MEM supplemented with 5% FBS (Atlanta Biologicals, Atlanta, GA), vitamins (1x), nonessential amino acids (1x), penicillin-streptomycin antibiotics (1 x), sodium pyruvate (1x), and L-glutamine (1x), all from Invitrogen (Carlsbad, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NANOG family is comprised of the original NANOG gene and ten associated pseudogenes (P1-P10). Recently, researchers have shown increased expression levels of NANOGP8 in glioblastoma cancer stem cells and have suggested that NANOGP8 may participate in the reprogramming of normal cells into cancerous states [ 10 , 11 ]. Furthermore, various studies have also reported increased expression levels of NANOG in cancer stem cells in other types of cancers, such as breast and lung cancers, supporting that NANOG and NANOGP8 are established cancer markers [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%